Search for blocks/addresses/...

Proofgold Asset

asset id
45ff3d9d10e34f620e0694c38ca670557a336de769967f840d69c5ff7b480eef
asset hash
f2d7533e02eb13241374405796a23d713def388faa5d6a0f2d023a4870ea807b
bday / block
27231
tx
6e2e4..
preasset
doc published by Pr5Zc..
Known 75b00.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x2 x7))))
Known d3b84.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x4 (x1 x7 (x1 x5 (x1 x2 (x1 x8 (x1 x3 x9))))))
Theorem d1680.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x6 (x1 x2 (x1 x9 (x1 x3 x4))))))
...

Theorem 3e838.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x6 (x1 x2 (x1 x9 (x1 x3 x4))))))
...

Known c0c54.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x2 x8)))))
Known 94a25.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x8 (x1 x3 (x1 x6 (x1 x2 (x1 x4 (x1 x5 x9))))))
Theorem a18fe.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x6 (x1 x2 (x1 x4 x3))))))
...

Theorem 3bead.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x6 (x1 x2 (x1 x4 x3))))))
...

Theorem a8bbd.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x6 (x1 x2 (x1 x3 x4))))))
...

Theorem 009b9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x6 (x1 x2 (x1 x3 x4))))))
...

Known 2c881.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x6 (x1 x3 (x1 x8 (x1 x2 (x1 x4 (x1 x5 x9))))))
Theorem f4806.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x4 (x1 x2 (x1 x6 x3))))))
...

Theorem 6c904.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x4 (x1 x2 (x1 x6 x3))))))
...

Known 45f87.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 . x0 x2x0 x3x0 x4x0 x5x1 x2 (x1 x3 (x1 x4 x5)) = x1 x3 (x1 x4 (x1 x2 x5))
Known 3373e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x8 (x1 x6 (x1 x3 (x1 x2 (x1 x4 (x1 x5 x9))))))
Theorem 1b50f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x4 (x1 x2 (x1 x3 x6))))))
...

Theorem a7ef9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x4 (x1 x2 (x1 x3 x6))))))
...

Theorem 55764.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x3 (x1 x2 (x1 x6 x4))))))
...

Theorem 6aa31.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x3 (x1 x2 (x1 x6 x4))))))
...

Known 95a8a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x6 (x1 x8 (x1 x3 (x1 x2 (x1 x4 (x1 x5 x9))))))
Theorem 45139.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x3 (x1 x2 (x1 x4 x6))))))
...

Theorem 6799b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x3 (x1 x2 (x1 x4 x6))))))
...

Known 63d4c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x4 (x1 x7 (x1 x8 (x1 x2 (x1 x3 (x1 x5 x9))))))
Theorem 5b304.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x3 (x1 x6 x4))))))
...

Theorem f36ae.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x3 (x1 x6 x4))))))
...

Known c5615.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x5 (x1 x7 (x1 x8 (x1 x2 (x1 x3 (x1 x4 x9))))))
Theorem bde03.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x3 (x1 x4 x6))))))
...

Theorem 4dfa1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x3 (x1 x4 x6))))))
...

Theorem 9e42c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x4 (x1 x6 x3))))))
...

Theorem d6fb2.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x4 (x1 x6 x3))))))
...

Known fd150.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x5 (x1 x7 (x1 x8 (x1 x2 (x1 x4 (x1 x3 x9))))))
Theorem 94bcf.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x4 (x1 x3 x6))))))
...

Theorem ea429.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x4 (x1 x3 x6))))))
...

Known f687d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x4 (x1 x7 (x1 x8 (x1 x2 (x1 x5 (x1 x3 x9))))))
Theorem 4500d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x6 (x1 x4 x3))))))
...

Theorem 0af91.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x6 (x1 x4 x3))))))
...

Theorem 911a0.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x6 (x1 x3 x4))))))
...

Theorem 9c340.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x8 (x1 x9 (x1 x2 (x1 x6 (x1 x3 x4))))))
...

Known a508b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x8 (x1 x3 (x1 x7 x9))))))
Theorem 7fa70.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x3 (x1 x8 x4))))))
...

Theorem 754e6.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x3 (x1 x8 x4))))))
...

Known 61514.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x3 (x1 x4 x9))))))
Theorem 6b45c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x3 (x1 x4 x8))))))
...

Theorem b2c18.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x3 (x1 x4 x8))))))
...

Theorem 0ff88.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x4 (x1 x8 x3))))))
...

Theorem 26646.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x4 (x1 x8 x3))))))
...

Known 08967.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x4 (x1 x3 x9))))))
Theorem fbc89.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x4 (x1 x3 x8))))))
...

Theorem f6ae0.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x4 (x1 x3 x8))))))
...

Known 20873.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x8 (x1 x7 (x1 x3 x9))))))
Theorem 731f4.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x8 (x1 x4 x3))))))
...

Theorem 631af.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x8 (x1 x4 x3))))))
...

Theorem b2cf2.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x8 (x1 x3 x4))))))
...

Theorem 0dda0.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x9 (x1 x8 (x1 x3 x4))))))
...

Known b35e9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x7 (x1 x3 x8)))))
Theorem f9e09.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x3 (x1 x9 x4))))))
...

Theorem a43d7.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x3 (x1 x9 x4))))))
...

Theorem fb4b4.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x4 (x1 x9 x3))))))
...

Theorem 2dba9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x4 (x1 x9 x3))))))
...

Known 51e9c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x7 (x1 x8 (x1 x3 x9))))))
Theorem b9834.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x9 (x1 x4 x3))))))
...

Theorem 38ccc.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x9 (x1 x4 x3))))))
...

Theorem 2275d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x9 (x1 x3 x4))))))
...

Theorem 43dd5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x8 (x1 x9 (x1 x3 x4))))))
...

Known 464e9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x3 x8)))))
Theorem 4ae89.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x3 (x1 x9 x8))))))
...

Theorem 922f8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x3 (x1 x9 x8))))))
...

Known 0f4fc.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x3 x7))))
Theorem f0e58.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x8 (x1 x9 x3))))))
...

Theorem 49a68.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x8 (x1 x9 x3))))))
...

Known 843b0.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x3 (x1 x8 (x1 x7 x9))))))
Theorem ae7c9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x9 (x1 x8 x3))))))
...

Theorem f8e21.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x9 (x1 x8 x3))))))
...

Known cfed3.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x8 (x1 x3 x9))))))
Theorem 79c6d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x9 (x1 x3 x8))))))
...

Theorem a5b31.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x4 (x1 x9 (x1 x3 x8))))))
...

Known 3b263.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x4 x8)))))
Theorem f56f8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x4 (x1 x9 x8))))))
...

Theorem 4ed3d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x4 (x1 x9 x8))))))
...

Theorem d2792.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x8 (x1 x9 x4))))))
...

Theorem d1840.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x8 (x1 x9 x4))))))
...

Theorem b3f36.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x9 (x1 x8 x4))))))
...

Theorem e9dbb.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x9 (x1 x8 x4))))))
...

Known 32caa.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x8 (x1 x4 x9))))))
Theorem 35338.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x9 (x1 x4 x8))))))
...

Theorem f5baa.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x2 (x1 x3 (x1 x9 (x1 x4 x8))))))
...

Known c1fcf.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x4 (x1 x2 x8)))))
Theorem 466f8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x4 (x1 x2 (x1 x9 x8))))))
...

Theorem ea8a6.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x4 (x1 x2 (x1 x9 x8))))))
...

Known b361b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x4 x8)))))
Theorem b2765.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x4 (x1 x9 x8))))))
...

Theorem d1895.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x4 (x1 x9 x8))))))
...

Known 5b962.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x6 (x1 x4 (x1 x5 (x1 x3 (x1 x2 x7))))
Theorem 9c439.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x8 (x1 x9 x4))))))
...

Theorem a6794.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x8 (x1 x9 x4))))))
...

Known 7eb11.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x4 (x1 x5 (x1 x3 (x1 x2 (x1 x8 (x1 x7 x9))))))
Theorem 1e240.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x9 (x1 x8 x4))))))
...

Theorem ba465.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x9 (x1 x8 x4))))))
...

Known 4195b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x8 (x1 x4 x9))))))
Theorem 1ebe4.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x9 (x1 x4 x8))))))
...

Theorem 0c44b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x3 (x1 x2 (x1 x9 (x1 x4 x8))))))
...

Known ead36.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x3 (x1 x4 (x1 x2 (x1 x8 (x1 x6 x9))))))
Theorem c877e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x9 (x1 x2 (x1 x8 x3))))))
...

Theorem d2253.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x9 (x1 x2 (x1 x8 x3))))))
...

Known a0f12.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x8 (x1 x2 (x1 x3 x9))))))
Theorem 79f99.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x9 (x1 x2 (x1 x3 x8))))))
...

Theorem ba054.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x9 (x1 x2 (x1 x3 x8))))))
...

Known dd178.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x5 (x1 x3 (x1 x4 (x1 x2 (x1 x6 x8)))))
Theorem 49f41.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x8 (x1 x2 (x1 x9 x3))))))
...

Theorem b8f03.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x8 (x1 x2 (x1 x9 x3))))))
...

Known 9b9fe.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x3 (x1 x2 x8)))))
Theorem 2b1d6.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x3 (x1 x2 (x1 x9 x8))))))
...

Theorem 5358e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x3 (x1 x2 (x1 x9 x8))))))
...

Known fa965.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x3 x8)))))
Theorem 03d07.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x3 (x1 x9 x8))))))
...

Theorem 4b858.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x3 (x1 x9 x8))))))
...

Theorem 4a127.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x8 (x1 x9 x3))))))
...

Theorem 3fa65.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x8 (x1 x9 x3))))))
...

Theorem 42f1d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x9 (x1 x8 x3))))))
...

Theorem 52346.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x9 (x1 x8 x3))))))
...

Known 7d315.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x8 (x1 x3 x9))))))
Theorem 14152.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x9 (x1 x3 x8))))))
...

Theorem a16f7.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x9 (x1 x3 x8))))))
...

Known a8835.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x8 (x1 x3 (x1 x4 (x1 x2 (x1 x5 (x1 x6 x9))))))
Theorem 09975.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x9 (x1 x2 (x1 x4 x3))))))
...

Theorem 223d2.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x9 (x1 x2 (x1 x4 x3))))))
...

Theorem c4365.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x9 (x1 x2 (x1 x3 x4))))))
...

Theorem 58469.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x9 (x1 x2 (x1 x3 x4))))))
...

Known e1a7b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x4 (x1 x2 (x1 x5 x8)))))
Theorem 96fd5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x4 (x1 x2 (x1 x9 x3))))))
...

Theorem 96e2a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x4 (x1 x2 (x1 x9 x3))))))
...

Theorem 9698b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x3 (x1 x2 (x1 x9 x4))))))
...

Theorem 77e96.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x3 (x1 x2 (x1 x9 x4))))))
...

Known 7a93b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x4 (x1 x5 (x1 x7 (x1 x2 (x1 x3 x8)))))
Theorem bd217.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x2 (x1 x3 (x1 x9 x4))))))
...

Theorem 59272.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x2 (x1 x3 (x1 x9 x4))))))
...

Theorem 7e7d0.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x2 (x1 x4 (x1 x9 x3))))))
...

Theorem e600d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x2 (x1 x4 (x1 x9 x3))))))
...

Known 46ed9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x6 (x1 x4 (x1 x5 (x1 x7 (x1 x2 (x1 x8 (x1 x3 x9))))))
Theorem a445b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x2 (x1 x9 (x1 x4 x3))))))
...

Theorem 89af9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x2 (x1 x9 (x1 x4 x3))))))
...

Theorem e0206.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x2 (x1 x9 (x1 x3 x4))))))
...

Theorem 220ba.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x8 (x1 x2 (x1 x9 (x1 x3 x4))))))
...

Known f4d3a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x8 (x1 x3 (x1 x4 (x1 x2 (x1 x6 (x1 x5 x9))))))
Theorem 54ada.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x9 (x1 x8 (x1 x2 (x1 x4 x3))))))
...

Theorem 18627.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 x9 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x0 x9x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 (x1 x8 x9)))))) = x1 x7 (x1 x5 (x1 x6 (x1 x9 (x1 x8 (x1 x2 (x1 x4 x3))))))
...